FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENCEGAHAN DERMATITIS KONTAK PADA NELAYANDI WILAYAH BATANG KAPAS KABUPATEN PESISIR SELATAN TAHUN 2022 - Susilaningsih, Dewi (Ensiklopedia of Journal, 2023)
Dermatitis is skin inflammation in response to exogenous and endogenous factors causing clinical abnormalities in the form of polymorphic efflorescence. The incidence of dermatitis in 2022 in the Batang Kampang area is 50%. The aim of this study was to determine factors related to contact dermatitis prevention behavior in Fishermen in the Batang Kapas area of Pesisir Selatan Regency in 2022. The research method used is quantitative using an analytical descriptive method. This research was conducted in the Batang Kapas area of Pesisir Selatan Regency in July 2022. The population in this research was a group of 452 fishermen, while the sample was taken using the slovin formula using a simple random sampling technique of 82 respondents. Data were analyzed univariately in the form of frequency distribution and bivariately using the Chi-Square test. The results showed that more than half (69.5%) had poor prevention of dermatitis, more than half (62.2%) had a low level of knowledge, more than half (67.1%) had a negative attitude, more than half (72%) personal hygiene not good. there is a relationship between knowledge level and prevention of dermatitis (p=0.000), there is a relationship between attitude and prevention of dermatitis in fishermen (p=0.000), there is a relationship between personal hygiene and prevention of dermatitis (p=0.003). Based on the results of the study that there is a relationship between the level of knowledge, attitude and personal hygiene with the prevention of dermatitis in fishermen. Suggestions, it is hoped that all fishermen can overcome dermatitis and maintain good personal hygiene.